METHODS FOR ASSESSING THE EFFECTIVENESS OF ECONOMIC ACTIVITIES OF BUSINESSES WITH THE ENVIRONMENTAL ASPECT - Svetlana A. Lankina; Tatiana E. Platonova (Статистика и экономика, 2016)
The article describes the methodological approaches to evaluating the effectiveness of economic activities of businesses, taking into account the environmental aspect, presented the problem and the factors affecting the economic interest in the environmental performance of the enterprise.